(Re)developing old apartment blocks in Hanoi: government vision, local resistance and spatial routines. Issue 4 (4th July 2019) - Phuong, Dinh Quoc
ABSTRACT: This article examines experiences from redevelopments of old housing estate in Hanoi via a case study of old Soviet-style apartment estates (KTT), which represents one important layer of the city's built environment. As redevelopment of these housing estates have recently attached attention from local public and media, this article looks at the recent practices and challenges facing by local government, property developers and residents whose involvement and tensions will be also examined to have a better understanding of the nature of changes as well as local struggles in their making and remaking of housing environments. Implication from this study of Hanoi's KTTs will hopefully help informing policy-makers and designers in making technical planning and housing strategies for redevelopment projects in Vietnam and other Asian cities with similar social and cultural contexts.